Quality evaluation of lassi sold in Kolhapur city - Munde, BB; Patange, DD; Shendurse, Ashish Maruti; Kamble, DK; Sawale, Pravin Digambar (Indian Journal of Dairy Science, 2017)
Lassi of various brands are been prepared and marketed in Kolhapur city of Maharashtra. On the basis of preliminary survey, the most popular six brands of lassi were selected and coded with KS1, KS2, KS3, KS4, KS5 and KS6 which were brought to the laboratory under chilled condition. The sensory, physico-chemical and microbial qualities of lassi were studied. Colour and appearance, body and texture, flavour, consistency and overall acceptability were significantly (P